The Creating Share Value communication of PT. Bio Farma in green livestock feed empowerment program - Mansyur Mansyur; Sarmedi Sarmedi; Tendry Firmansyah; Agus Rahmat (Jurnal Kajian Komunikasi, 2022)
One of the flagship Creating Share Value (CSV) programs by PT Biofarma in 2021 is the Re-Grass & Sustainability Village program. First, this program has been able to meet the demand for fodder for horses, which is one of the input rows in the production process at PT. Biofarma and also for the farming community around PT Biofarma’s operations. Even the fostered community is able to supply the needs of green fodder for several breeders in other areas through fermentation activities (silage) and pellet feed. Second, the CSR program to build animal feed security also received MURI records for productivity and high protein content. Third, the results of the evaluation by calculating the value of Social Return on Investment (SROI) show the value of Rp. 7,37. Based on the indicators, there are questions about what kind of communication was built into the program so that it was able to achieve a high level of success. Research with qualitative methods was conducted to answer the questions. The results of the research show that the communication activities carried out include the integration and coordination of various channels and sources of information, designing and implementing various communication techniques, and utilizing the nature and characteristics of communicators according to their respective positions. Implementation of information diffusion of green fodder is also supported by facilities that can simplify and reduce the risk of loss to the target group in adopting innovations.